1967
DOI: 10.1192/bjp.113.498.491
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Ideas of Sexual Change in Female Schizophrenics

Abstract: A previous study of the incidence of subjective ideas of sexual change in male schizophrenics has briefly noted the lack of precise quantified data in the literature and the standard English language teaching texts (Gittleson and Levine, 1966). There are no controlled studies of these ideas in female schizophrenics. The studies of Klaf and Davis (1960), Planansky and Johnston (1962) and Lukianowicz (1963) refer only to males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
4

Year Published

1974
1974
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 5 publications
1
13
0
4
Order By: Relevance
“…DSM-IV states that "delusions of belonging to the other sex" (p. 537) are rarely seen in schizophrenia, but this claim is difficult to reconcile with studies showing that about 25% of patients with schizophrenia experience cross-gender identification at some point in their life (8)(9)(10)(11). In line with this, for a diagnosis of gender identity disorder (previously termed "transsexualism"), DSM-III required that the symptoms were "not due to another mental disorder, such as Schizophrenia" (p. 264).…”
Section: (Am J Psychiatry 2003; 160:1332-1336)mentioning
confidence: 95%
“…DSM-IV states that "delusions of belonging to the other sex" (p. 537) are rarely seen in schizophrenia, but this claim is difficult to reconcile with studies showing that about 25% of patients with schizophrenia experience cross-gender identification at some point in their life (8)(9)(10)(11). In line with this, for a diagnosis of gender identity disorder (previously termed "transsexualism"), DSM-III required that the symptoms were "not due to another mental disorder, such as Schizophrenia" (p. 264).…”
Section: (Am J Psychiatry 2003; 160:1332-1336)mentioning
confidence: 95%
“…Some studies used broad categories such as positive versus negative (Andrew et al, 2008; Close & Garety, 1998). Others have examined more specific content such as sexual (Gittleson & Dawson-Butterworth, 1967; Gittleson & Levine, 1966; Thompson et al, 2010), or content observed in auditory hallucinations (Honig et al, 1998). Studies often vary in the use of the same term, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted, however, that these four experiments did not explicitly seek to model a discrete clinical delusion (even though clinical patients with sex change delusion have been reported; see Borras, Huguelet, & Eytan, 2007;Gittleson & Dawson-Butterworth, 1967;Gittleson & Levine, 1966).…”
Section: Sex Change Delusionmentioning
confidence: 95%